Pengaruh Pijat Effluarge Dan Accupresure Sp6 Terhadap Dismenorhea Primer Pada Akseptor Kb Iud Di Wilayah Kerja Puskesmas Maracang Kabupaten Purwakarta Tahun 2024 - Khalifah, Intan Noor (CV. Green Publisher Indonesia, 2025)
Dysmenorrhea is the most common complaint felt by mothers who accept birth control IUDs in the first year of installation. Treatment of dysmenorrhea can be done with pharmacological and non-pharmacological therapies. Non-pharmacological therapy to reduce dysmenorrhea pain through safer and cost-efficient efluarge and accupresure SP 6 massage. Objective: The effect of effluarge massage and accupresure SP6 on primary dysmenorrhea is known in IUD birth control acceptors in the Working Area of the Maracang Health Center, Purwakarta Regency in 2024. The target of this study is the IUD birth control acceptor Method: The type of research used is a quasi-experimental experiment by conducting a pre and posttest approach of two group design. The study subjects were divided into two groups, namely 18 people who were given effluarge massage and 18 people who were given SP6 acupressure. The average level of pain before intervention in the effleurage massage group was 7.05 ± 0.88 and after the intervention decreased to 4.22 ± 0.73. The results of the statistical test showed a p-value of 0.001, which means that there is a significant difference between the level of pain before and after the effleurage massage. Meanwhile, in the SP6 acupressure point group, the average pain level before the intervention was 7.33 ± 0.79, and after the intervention decreased to 3.44 ± 0.67. The statistical test yielded a p-value of 0.000, which also showed a very significant difference between before and after the intervention. Conclusion: The results of this statistical test prove that effleurage massage and acupressure SP6 are effective in reducing the level of primary dysmenorrhea pain in IUD birth control acceptors in the work area of the Maracang Health Center in 2024